Hijabophobia: a closed eye challenge towards Muslim friendly hospitality services in Malaysia - Mohd. Zain, Nor Razinah; Hassan, Rusni; Finieli, Salsabilla Terra (USIM, 2018)
This research analyses the existence of hijabophobia in relation to Muslim-friendly hospitality services in Malaysia. By looking into the current practices of hospitality industry (specifically by looking into customer services of hotels) in Malaysia, this research investigates: (i) what is meant by hijabophobia? (ii) nature of hijabophobia under the purview of Malaysian laws; (iii) the impacts of hijabophobia in the employments and customer services; and (iv) the countermeasures to eliminate hijabophobia in the hospitality industry in Malaysia. This exploratory research utilises the doctrinal legal methods and the collected real experiences that are obtained through qualitative interviews. Based on the researchers’ preliminary investigation, there is existence of hijabophobia in the customer services of hotels and their employment in Malaysia. Such existence of hijabophobia is promoted through the hotels’ policies; and sometimes under unwritten but well acceptable standard of operations and practices. Unfortunately, since this research is carried out only based on preliminary findings, the researchers are unable to provide the frequency of occurrences for the hijabophobic practices in their customer services or employments. Here, the researchers suggest for an in-depth investigation on the policies and standard of operation or practices of each and every hotels in Malaysia. This is also necessary to evaluate the extent of Muslim-friendly hospitality services applied in these hotels.